2003
DOI: 10.1111/j.1747-5457.2003.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Oil Accumulations in the Upper Jurassic Bazhenov Black Shale Formation, West Siberian Basin: A Self‐sourced Reservoir System

Abstract: The Upper Jurassic Bazhenov Formation in the central West Siberian Basin is a classic marine black shale unit containing abundant Type II kerogen with high oil‐generation potential. These shales source around 90% of the oil in the West Siberian Basin. They also contain oil accumulations in unconventional self‐sourced reservoirs. Reservoir zones are generally small and are located along fault planes. Primary oil migration was focused along fracture networks adjacent to the fault zones. Oil charging took place i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…Clay minerals, especially illite (Schettler and 27 Parmely, 1991), have also been documented as possessing micropore structures capable of sorbing gas 28 (Gasparik et al, 2012). In addition to sorption on particle surfaces, petroleum storage in the pores of either 29 organic (Loucks et al, 2009) or inorganic (Han et al, 2015) origin have been documented, as well as natural 30 fractures (Lopatin et al, 2003;Pollastro, 2010). 31 Organic pore development is believed to be largely due to the thermal cracking of kerogen (Jarvie et al,32 2007; Loucks et al, 2009) and/or bitumen (Bernard et al, 2012b), though primary organic pores have been 33 observed within immature organic matter as well (Löhr et al, 2015;Pommer and Milliken, 2015).…”
mentioning
confidence: 99%
“…Clay minerals, especially illite (Schettler and 27 Parmely, 1991), have also been documented as possessing micropore structures capable of sorbing gas 28 (Gasparik et al, 2012). In addition to sorption on particle surfaces, petroleum storage in the pores of either 29 organic (Loucks et al, 2009) or inorganic (Han et al, 2015) origin have been documented, as well as natural 30 fractures (Lopatin et al, 2003;Pollastro, 2010). 31 Organic pore development is believed to be largely due to the thermal cracking of kerogen (Jarvie et al,32 2007; Loucks et al, 2009) and/or bitumen (Bernard et al, 2012b), though primary organic pores have been 33 observed within immature organic matter as well (Löhr et al, 2015;Pommer and Milliken, 2015).…”
mentioning
confidence: 99%
“…Production to date is only from faulted zones, but there is potentially a very large resource. In one 40 000 km 2 area, the in-place resource is 8 Gb, of which 1.7 Gb could ultimately be recovered [18], but the total area of thermally mature Bazhenov Formation is close to 10 6 km 2 , and a recent Lukoil report indicates a recoverable resource of 80-160 Gb. Lukoil is said to be producing about 2000 b d −1 in initial experimental production.…”
Section: (Iii) Russiamentioning
confidence: 99%
“…A number of previous publications discussed the cross plot of Rock-Eval S1 against TOC (Lopatin et al, 2003;Jarvie 2012;Abrams, 2014;Raji et.al., 2015 in press). The relationship of S1 with TOC is more revealing (Figure 6), where the majority of Ͼ2%TOC samples (89.5%) fall below the cross-over line of Generation Index ϭ 100 (Jarvie, 2012) and are hence less likely to give high unconventional oil yields on fracking.…”
Section: Figure 4 -Maturity Trends For Toc (Wt%) Plus Rock-eval S1 Smentioning
confidence: 99%